Applied Analysis at MGIMO-University - A. A. Orlov; A. L. Chechevishnikov (Vestnik MGIMO-Universiteta)
Applied analysis of international relations began to form at MGIMO-University in the 1970s. This kind of research always attracted considerable interest of the Ministry of Foreign Affairs of the USSR, and other executive institutions of the government and received their support. The Ministry of Foreign Affairs initiated the creation of a special unit at MGIMO - the Problem Research Laboratory of Systems Analysis in International Relations. The Laboratory was using system analysis and quantitative methods to produce scientific information for decision-makers to make "more informed decisions in the field of international relations in order to reduce the level of uncertainty in the assessment of the expected impact of these decisions". In 2004, the successor to the Problem Laboratory - Center for International Studies - was transformed into a Research Coordination Council for International Studies, which in 2009 handed its functions to the Institute of International Studies. In comparison with previous periods the Institute of International Studies has significantly increased of research for the Ministry of International Affairs. It has also moved functionally outside its institutional boundaries and produces unclassified research for public offer. It also serves as a place for vivid public discussions among IR specialists. There's also an international recognition of the Institute of International Studies. The "Go to think tanks" international ranking produced annually at the University of Pennsylvania has put MGIMO-University on the 10th place in the category of university based think tanks.